Ticagrelor induces angiogenesis in progenitor and mature endothelial cells in vitro: investigation of the possible role of adenosine - Sidiropoulou, Sofia; Gatsiou, Aikaterini; Hansson, Kenny M.; Tsouka, Aikaterini N.; Stellos, Konstantinos; Tselepis, Alexandros D. (International journal of molecular sciences, 2024)
Ticagrelor, a reversible platelet P2Y12 receptor antagonist, exerts various pleiotropic actions, some of which are at least partially mediated through adenosine. We studied the ticagrelor and adenosine effect on the angiogenic properties of progenitor CD34+-derived endothelial colony-forming cells (ECFCs). Angiogenesis studies were performed in vitro using capillary-like tube formation and spheroid-based angiogenesis assays. The effects of adenosine receptor antagonists, including DPCPX (A1 antagonist), SCH58621 (A2A antagonist), MRS1706 (A2B inverse agonist and antagonist), MRS1220 (A3 antagonist) and adenosine deaminase (ADA), were also investigated. Ticagrelor, adenosine, and their combination increased capillary-like tube formation and spheroid sprout formation by ECFCs in a dose-dependent manner. This effect was significantly reduced by SCH58621, MRS1706, and their combination, as well as by ADA. By contrast, DPCPX and MRS1220 did not exhibit any inhibitory effects. Similar results were obtained when mature human umbilical vein endothelial cells (HUVECs) were studied. These results show that ticagrelor stimulates angiogenesis by progenitor and mature endothelial cells in an adenosine-dependent pathway in which the adenosine receptors A2A and A2B play major roles. The significance of these results at the clinical level in patients with atherothrombotic events and treated with ticagrelor needs to be investigated.